Knowledge and Attitude regarding Oral Cancer among Proficiency Certificate Level General Medicine Students in Bharatpur, Chitwan, Nepal - Neupane, Laxmi; Ale, Yam Kumari; Upadhyay, Hari Prasad (Nepalese Journal of Cancer, 2026)
Introduction: Oral cancer is one of the most common cancer worldwide. Medical students can play a major role in recognizing oral mucosal changes that may lead to cancer. The objective of the study is to find out the knowledge and attitude among General Medicine (GM) students in Bharatpur, Chitwan, Nepal.Methods: A descriptive cross-sectional study was conducted among General Medicine (GM) students in Bharatpur, Chitwan. Nepal. was used. A self-administered structured questionnaire was distributed to collect data among 114 students. Data were analyzed by using SPSS version 22. Descriptive and inferential statistics were calculated.Results: The age of respondents ranged from 17 to 35 years, with a mean and standard deviation 20.01+2.455. Most of the respondents were male 58.8%, from Madhesh province 62.3%, unmarried 95.6%, followed by Hindu religion 91.2% and of Madhesi ethnicity 69.3%. The majority (83.3%) of respondents know the meaning of oral cancer. The overall level of knowledge towards oral cancer was good among 56.1% and a positive attitude was 57.9%. There is no association between level of knowledge and level of attitude (p=0.526). Respondents with a low level of knowledge demonstrated an equal distribution of positive and negative attitudes toward oral cancer. However, a majority of respondents with high and moderate levels of knowledge exhibited a positive attitude, accounting for 62.5% and 52.4% respondents, respectively.Conclusion: knowledge and attitude of General Medicine students towards oral cancer is just over the half, so, it needs to be improved and the concerned authority needs to pay more attention on education of students who are considered to be the future primary health care providers.